Sheet, metal-clad laminate, substrate for circuit, and antenna
By using a sheet with fluororesin and filler particles, surface-treated to enhance oxygen content, the challenges of achieving high adhesion to copper foils with low dielectric loss and expansion coefficient in high-frequency printed wiring boards are addressed, resulting in improved adhesion and peel strength.
Patent Information
- Application Number
- JP2024125886
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-08-01
- Publication Date
- 2025-03-21
Smart Images

Figure 2025039524000001 
Figure 2025039524000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sheet, a metal clad laminate, a circuit board, and an antenna. [Background technology]
[0002] There is a demand for high frequency printed wiring boards with small transmission loss, and it is known to use a fluororesin film in such high frequency printed wiring boards (Patent Document 1, etc.).
[0003] In such printed wiring boards, the fluororesin film is subjected to a surface treatment to improve its adhesion to the copper foil. Patent Document 2 proposes that the fluororesin film is subjected to a surface treatment and an annealing treatment to improve its adhesion to the copper foil. Patent Document 3 also proposes that a composition can be obtained that can optimally exhibit the properties of inorganic particles by containing particles containing a tetrafluoroethylene-based polymer and composite particles having a first inorganic particle as a core and a second inorganic particle as a shell, the second inorganic particle having an average particle size smaller than that of the first inorganic particle and an aspect ratio larger than that of the first inorganic particle. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-8260 A [Patent Document 2] Patent Publication No. 2022-112028 [Patent Document 3] JP 2023-28091 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present disclosure is to obtain a sheet that exhibits high adhesion to copper foil and the like while maintaining a low dielectric tangent (Df) and a low coefficient of linear expansion (CTE), and a metal clad laminate using the same. [Means for solving the problem]
[0006] The present disclosure relates to a sheet containing a fluororesin and two or more types of filler particles, characterized in that the oxygen element ratio on one or both sides is 3.0 atomic% or more when measured by X-ray photoelectron spectroscopy (XPS), and the coefficient of linear expansion (CTE) is 70 ppm / °C or less.
[0007] The fluororesin is preferably polytetrafluoroethylene. Furthermore, it is preferable that the nitrogen element ratio on the surface of the sheet is 0.85 atomic % or more when measured by XPS. Furthermore, it is preferable that the sheet has a silicon element ratio of 0.5 atomic % or more on the above-mentioned surface as measured by XPS.
[0008] Furthermore, it is preferable that the sheet has a static contact angle of 105° or less on the surface of the sheet, the static contact angle being measured 1 second after a 2 μL droplet is deposited on the sheet.
[0009] It is preferable that one of the two or more types of filler particles is silica particles. The silica particles are preferably spherical silica. As the silica particles, it is preferable to use silica particles treated with a silane coupling agent. The silica particles preferably have an average particle size of 10 μm or less.
[0010] It is preferable that the filler particles other than the silica particles of the two or more types of filler particles are alumina particles. The alumina particles preferably have an average particle size of 10 μm or less. The mass ratio of the alumina particles to the total amount of the silica particles and the alumina particles is preferably 10% by mass to 50% by mass. The content of the silica particles and alumina particles in the total amount of the sheet is preferably 30% by mass or more.
[0011] The sheet preferably has a dielectric loss tangent value of 0.0015 or less at 10 GHz. The sheet preferably has a thickness of 5 to 250 μm.
[0012] The present disclosure also relates to a method for producing the sheet, which comprises mixing fluororesin particles, silica particles, and alumina particles to form a film, and then performing surface treatment. The present disclosure also provides a method for producing a sheet, which comprises forming a film using a composition substantially consisting of fluororesin particles and filler particles including at least silica particles and alumina particles, and performing a surface treatment.
[0013] The present disclosure also relates to a metal-clad laminate having the above-mentioned sheet as an essential layer and having a metal foil layer on one or both sides. The metal foil is preferably a copper foil. The surface roughness (Rz) of the copper foil is preferably 2.0 μm or less. The copper foil preferably has a surface roughness (Rq) of 0.01 to 0.15 μm. It is preferable that the copper foil and the sheet are directly laminated together, and the peel strength of the interface between the copper foil and the sheet is 1 kN / m or more.
[0014] The present disclosure also relates to a method for producing the copper clad laminate, which comprises laminating the sheet and copper foil, heating the laminate at 180 to 390°C, and press-molding the laminate at a pressure of 0.5 to 5 MPa under vacuum or in an inert gas atmosphere.
[0015] The present disclosure also relates to a circuit board having the metal clad laminate. The present disclosure is also an antenna formed from the circuit board. The antenna is preferably a millimeter wave antenna for mobility applications. Effect of the Invention
[0016] The sheet of the present disclosure exhibits high adhesion to metal foils such as copper foil while maintaining a low dielectric tangent (Df) and a low coefficient of linear expansion (CTE). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present disclosure will now be described in detail. In high-frequency boards for 5G and above, if the interface between the fluororesin sheet and the commonly used copper foil etc. is smooth, transmission loss is low and the characteristics of the high-frequency board are improved. Therefore, good adhesion between the fluororesin sheet and the copper foil etc. with a smooth surface is required.
[0018] However, sheets made of fluororesin alone have a high linear expansion coefficient, which may cause warping of the board or defects in the circuit. In particular, in sheets made of polytetrafluoroethylene (PTFE) resin alone, functional groups containing oxygen and the like are difficult to form even when surface treatment is performed, and therefore sufficient adhesion to copper foil, which has a smooth surface, is not obtained, and further improvement is required. Such problems arise because functional groups are difficult to generate on the surface of polytetrafluoroethylene resin, and the generated functional groups are also prone to molecular motion, so that the functional groups move from the surface to the inside of the resin and are difficult to be exposed to the surface, making it difficult to obtain the effects of surface treatment.
[0019] The present disclosure has discovered that by subjecting the surface of a sheet containing a fluororesin and two or more types of filler particles to a surface treatment such as plasma treatment and increasing the oxygen element ratio on the sheet surface, the sheet can be bonded well to a metal foil such as a copper foil having a smooth surface.
[0020] In particular, by incorporating silica particles as one of the filler particles, when the sheet is subjected to a surface treatment, the silica surface can also have functional groups derived from the surface treatment, and the oxygen atom ratio on the sheet surface can be increased, which improves the adhesion between the sheet and the metal foil and improves the peel strength of the adhesive surfaces. Furthermore, by containing alumina particles together with silica particles, the silica particles are present in greater amounts on the sheet surface, improving the adhesion between the sheet and the metal foil and increasing the peel strength.
[0021] Furthermore, the present disclosure uses a composite of fluororesin and filler particles to further reduce the coefficient of linear expansion (CTE) of the sheet, and can adequately suppress substrate warpage and circuit defects. Thus, the sheet of the present disclosure can achieve both a low coefficient of linear expansion and good peel strength.
[0022] The sheet of the present disclosure has an oxygen element ratio of 3.0 atomic % or more on one or both sides thereof as measured by X-ray photoelectron spectroscopy (XPS). In particular, the oxygen element ratio of the sheet surface that adheres to the metal foil as measured by X-ray photoelectron spectroscopy (XPS) should be 3.0 atomic % or more. By having the oxygen element ratio of 3.0 atomic % or more, the sheet bonds with the surface of the metal foil, improving the peel strength against the metal foil. The oxygen atomic ratio is preferably 3.0 atomic % or more, more preferably 5.0 atomic % or more, and even more preferably 10.0 atomic % or more. There is no particular upper limit, but in consideration of the effect on productivity and other physical properties, it is preferably 25.0 atomic % or less.
[0023] Specifically, the measurement by X-ray photoelectron spectroscopy (XPS) is carried out using a scanning X-ray photoelectron spectroscopic analyzer (XPS / ESCA) PHI5000VersaProbeII (manufactured by ULVAC-PHI, Inc.).
[0024] In the sheet of the present disclosure, in the surface having an oxygen element ratio of 3.0 atomic % or more as measured by X-ray photoelectron spectroscopy (XPS), the nitrogen element ratio is preferably 0.85 atomic % or more as measured by X-ray photoelectron spectroscopy (XPS). The nitrogen atomic ratio is more preferably 2.0 atomic % or more, further preferably 3.0 atomic % or more, and most preferably 4.0 atomic % or more. By increasing the nitrogen element ratio on the sheet surface, which contributes to adhesion, it is possible to obtain sufficient peel strength with the metal foil without impairing the dielectric properties. There is no particular upper limit, but in consideration of the effect on productivity and other physical properties, it is preferably 25.0 atomic % or less.
[0025] In the sheet of the present disclosure, in the surface having an oxygen element ratio of 3.0 atomic % or more as measured by X-ray photoelectron spectroscopy (XPS), the silicon element ratio is preferably 0.50 atomic % or more as measured by X-ray photoelectron spectroscopy (XPS). The silicon atomic ratio is more preferably 1.0 atomic % or more, further preferably 1.5 atomic % or more, and most preferably 2.0 atomic % or more. The silicon element ratio on the sheet surface as described above can be obtained when silica particles are used as one of the filler particles. In this way, the silicon element ratio on the sheet surface, which contributes to adhesion, is high, and the silica particles that can be surface-treated are exposed, which can increase the peel strength with the metal foil. There is no particular upper limit, but in consideration of the effect on other physical properties such as productivity and strength, it is preferably 10.0 atomic % or less.
[0026] In the sheet of the present disclosure, on a surface having an oxygen element ratio of 3.0 atomic% or more as measured by X-ray photoelectron spectroscopy (XPS), the static contact angle of water measured 1 second after landing with a droplet volume of 2 μL is preferably 105° or less, more preferably 103° or less, and even more preferably 100° or less. By satisfying such a range, new functional groups are generated in the sheet, and the peel strength with the metal foil is increased.
[0027] The static contact angle of water was measured using a contact angle meter (Kyowa Interface Science Co., Ltd., "DropMaster") at 23° C., with a droplet volume of 2 μL, and one second after the droplet landed.
[0028] The sheet of the present disclosure has a coefficient of linear expansion (CTE) of not more than 70 ppm / ° C. Having a CTE within the above range is preferable in that the sheet has low shrinkage and excellent dimensional stability. The upper limit is more preferably 50 ppm / ° C., and even more preferably 40 ppm / ° C. The lower limit is preferably 10 ppm / ° C., and more preferably 18 ppm / ° C.
[0029] The linear expansion coefficient in this specification is determined by performing TMA measurement in a tensile mode using a TMA-7100 (manufactured by Hitachi High-Tech Science Corporation), using a sheet cut to a length of 20 mm, width of 5 mm and thickness of 150 μm as a sample piece, setting the chuck distance to 10 mm, applying a load of 49 mN, and measuring the displacement of the sample from 0 to 150°C at a heating rate of 2°C / min.
[0030] (Fluorine resin) Fluorine resins have low dielectric properties and can therefore be suitably used in the present disclosure.
[0031] The fluororesin that can be used in the present disclosure is not particularly limited, and examples thereof include polytetrafluoroethylene (PTFE), tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP], TFE / alkyl vinyl ether copolymer [PFA], TFE / HFP / alkyl vinyl ether copolymer [EPA], TFE / chlorotrifluoroethylene [CTFE] copolymer, TFE / ethylene copolymer [ETFE], polyvinylidene fluoride [PVdF], tetrafluoroethylene having a molecular weight of 300,000 or less [LMW-PTFE], etc. These fluororesins may be used alone or in combination of two or more. Among them, polytetrafluoroethylene (PTFE) is particularly preferable from the viewpoint of low dielectric properties and low linear expansion coefficient. PTFE having fibrillation is preferable. PTFE having fibrillation means PTFE that can be paste-extruded from unsintered polymer powder.
[0032] The PTFE may be modified polytetrafluoroethylene (hereinafter referred to as modified PTFE), homopolytetrafluoroethylene (hereinafter referred to as homoPTFE), or a mixture of modified PTFE and homoPTFE. From the viewpoint of maintaining good moldability of polytetrafluoroethylene, the content of modified PTFE in the polymeric PTFE is preferably 10% by mass or more and 98% by mass or less, and more preferably 50% by mass or more and 95% by mass or less.
[0033] The homo-PTFE is not particularly limited, and homo-PTFE disclosed in JP-A-53-60979, JP-A-57-135, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345 pamphlet, WO 2007 / 119829 pamphlet, WO 2009 / 001894 pamphlet, WO 2010 / 113950 pamphlet, WO 2013 / 027850 pamphlet, etc. can be suitably used. Among these, homo-PTFE having high stretchability and disclosed in JP-A-57-135, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345, WO 2007 / 119829, WO 2010 / 113950 and the like is preferred.
[0034] The modified PTFE is composed of TFE and a monomer other than TFE (hereinafter referred to as a modified monomer). The modified PTFE may be, but is not limited to, one that is uniformly modified by the modified monomer, one that is modified at the beginning of the polymerization reaction, one that is modified at the end of the polymerization reaction, etc. The modified PTFE is preferably a TFE copolymer obtained by subjecting a small amount of a monomer other than TFE to polymerization together with TFE within a range that does not significantly impair the properties of the TFE homopolymer.
[0035] The modified PTFE may be, for example, those disclosed in JP-A-60-42446, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-64-1711, JP-A-2-261810, JP-A-11-240917, JP-A-11-240918, WO 2003 / 033555 pamphlet, WO 2005 / 061567 pamphlet, WO 2007 / 005361 pamphlet, WO 2011 / 055824 pamphlet, WO 2013 / 027850 pamphlet, etc., which can be suitably used. Among these, modified PTFEs having high stretchability and disclosed in JP-A-61-16907, JP-A-62-104816, JP-A-64-1711, JP-A-11-240917, WO 2003 / 033555, WO 2005 / 061567, WO 2007 / 005361, WO 2011 / 055824 and the like are preferred.
[0036] The modified PTFE contains TFE units based on TFE and modified monomer units based on a modified monomer. The modified monomer units are a part of the molecular structure of the modified PTFE and are derived from the modified monomer. The modified PTFE contains the modified monomer units in an amount of preferably 0.001 to 0.500 mass%, more preferably 0.01 to 0.30 mass%, of the total monomer units. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE.
[0037] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene (HFP), chlorofluoroolefins such as chlorotrifluoroethylene (CTFE), hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride (VDF), perfluorovinyl ethers, perfluoroalkylethylenes (PFAE), ethylene, etc. The modifying monomer used may be one type or multiple types.
[0038] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorounsaturated compounds represented by the following general formula (1). CF2 = CF-ORf (1) (In the formula, Rf represents a perfluoro organic group.)
[0039] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.
[0040] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) (PAVE), which is represented by the above general formula (1) in which Rf is a perfluoroalkyl group having 1 to 10 carbon atoms. The perfluoroalkyl group preferably has 1 to 5 carbon atoms. Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, a perfluorohexyl group, etc. Preferred PAVEs are perfluoropropyl vinyl ether (PPVE) and perfluoromethyl vinyl ether (PMVE).
[0041] The perfluoroalkylethylene (PFAE) is not particularly limited, and examples thereof include perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), and the like.
[0042] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VDF, PAVE, PFAE and ethylene.
[0043] The fluororesin is preferably non-melt processable. Non-melt processable means that the resin does not have sufficient fluidity even when heated to the melting point or higher, and cannot be molded by a melt molding method generally used for resins. PTFE corresponds to this.
[0044] In the present disclosure, it is preferable to use particles of such non-melt-processable fluororesin and form them into a sheet by a molding method that fibrillates the particles. The molding method will be described later.
[0045] The PTFE preferably has a standard specific gravity (SSG) of 2.0 to 2.3. When such PTFE is used, a PTFE membrane having high strength (cohesion and puncture strength per unit thickness) is easily obtained. PTFE having a large molecular weight has a long molecular chain, and therefore it is difficult to form a structure in which the molecular chains are regularly arranged. In this case, the length of the amorphous part increases, and the degree of entanglement between the molecules increases. When the degree of entanglement between the molecules is high, the PTFE membrane is unlikely to deform under an applied load and is considered to exhibit excellent mechanical strength. In addition, when a PTFE having a large molecular weight is used, a PTFE membrane having a small average pore size is easily obtained.
[0046] The lower limit of the SSG is more preferably 2.05, and even more preferably 2.1.The upper limit of the SSG is more preferably 2.25, and even more preferably 2.2.
[0047] Standard specific gravity (SSG) was measured by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the resulting sample by the water displacement method.
[0048] In this embodiment, the molecular weight (number average molecular weight) of the PTFE constituting the PTFE particles is, for example, in the range of 2 million to 12 million. The lower limit of the molecular weight of the PTFE may be 3 million or 4 million. The upper limit of the molecular weight of the PTFE may be 10 million.
[0049] The number average molecular weight of PTFE can be measured by a method based on standard specific gravity and a method based on dynamic viscoelasticity when melted. The method based on standard specific gravity can be performed by a water displacement method based on ASTM D-792 using a sample molded based on ASTM D-4895 98. The method based on dynamic viscoelasticity is described, for example, by S. Wu in Polymer Engineering & Science, 1988, Vol. 28, 538 and the same document, 1989, Vol. 29, 273.
[0050] The PTFE preferably has a refractive index in the range of 1.2 to 1.6. By having such a refractive index, it is preferable in terms of low dielectric constant. The refractive index can be adjusted to be within the above range by a method of adjusting the polarizability or flexibility of the main chain. The lower limit of the refractive index is more preferably 1.25, more preferably 1.30, and most preferably 1.32. The upper limit of the refractive index is more preferably 1.55, more preferably 1.50, and most preferably 1.45.
[0051] The refractive indexes are values measured using a refractometer (Abbemat 300).
[0052] The PTFE preferably has a maximum endothermic peak temperature (crystalline melting point) of 340±7°C.
[0053] The PTFE may be a low-melting-point PTFE having a maximum peak temperature of 338°C or lower on an endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter, or a high-melting-point PTFE having a maximum peak temperature of 342°C or higher on an endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter.
[0054] The low melting point PTFE powder is a powder particle produced by emulsion polymerization, and has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.08 to 2.2, and a dielectric tangent (tan δ) of 1.9×10 -4~4.0×10 -4 Examples of commercially available products include Polyflon fine powders F201, F203, F205, F301, and F302 manufactured by Daikin Industries, Ltd., CD090 and CD076 manufactured by Asahi Glass Co., Ltd., and TF6C, TF62, and TF40 manufactured by DuPont.
[0055] The high melting point PTFE powder is also a powder particle produced by emulsion polymerization, and has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.0 to 2.1, and a dielectric tangent (tanδ) of 1.6×10 -4 ~2.2×10 -4 As commercially available products, for example, Polyflon fine powder F104 and F106 manufactured by Daikin Industries, Ltd., CD1, CD141, and CD123 manufactured by Asahi Glass Co., Ltd., and TF6 and TF65 manufactured by DuPont are listed.
[0056] The powder in which both PTFE polymer particles are secondary aggregated usually has an average particle size of 250 to 2000 μm. In particular, granulated powder obtained by granulation using a solvent is preferred from the viewpoint of improving the flowability when filling a mold during preforming.
[0057] Powder-shaped PTFE particles that satisfy the above-mentioned parameters can be obtained by a conventional manufacturing method, for example, by following the manufacturing methods described in International Publication No. 2015-080291 and International Publication No. 2012-086710.
[0058] (Filler particles) The sheet of the present disclosure must contain two or more types of filler particles. Although the specific mechanism has not been elucidated, by using two or more types of filler particles, one of the filler particles is more likely to be present on the sheet surface, and the sheet surface can have more functional groups derived from the surface treatment. Therefore, the adhesion between the sheet and the metal foil is improved, and the peel strength is increased. Examples of filler particles to be used include particles containing one or more inorganic fillers selected from silica, alumina, zinc oxide, tin oxide, titanium oxide, calcium carbonate, calcium oxide, magnesium oxide, ceramics, talc, mica, potassium titanate, calcium fluoride, boron nitride, barium sulfate, molybdenum disulfide, and potassium carbonate whiskers, and one or more organic fillers selected from polyphenyl ester, polyphenylene sulfide, polyimide, polyether ether ketone, polyphenylene, polyamide, and wholly aromatic polyester resins. Two or more of these may be used in combination.
[0059] The shape of the inorganic filler particles is not particularly limited, and may be, for example, spherical, plate-like, rod-like, scaly, needle-like, columnar, cone-like, frustum-like, polyhedral, cubic, hollow, etc. Spherical fillers are particularly preferred in that they have a small surface area, so that they can reduce the effect on the properties of the fluororesin, and also cause only a small degree of thickening when blended with a liquid.
[0060] The content of the two or more types of filler particles in the total amount of the sheet is preferably 30% by mass or more. This is preferable because it is possible to maintain a low dielectric constant and low loss while reducing the linear expansion coefficient. The blending amount is more preferably 35% by mass or more, even more preferably 50% by mass or more, and even more preferably 55% by mass or more. The upper limit of the blending amount of the filler particles is not particularly limited, but is preferably 70% by mass or less, more preferably 68% by mass or less, and even more preferably 65% by mass or less.
[0061] As the inorganic filler, at least two types selected from the group consisting of silica, alumina, titanium oxide, and talc are preferred, since they can further improve electrical properties, strength, heat resistance, and the like. In the present disclosure, it is preferable that one of the two or more types of filler particles is a silica particle, and it is also preferable that the filler particles other than the silica particles of the two or more types of filler particles are alumina particles.
[0062] By incorporating silica particles, when the sheet is subjected to a surface treatment, the silica surface can also have functional groups derived from the surface treatment, and therefore the oxygen atom ratio on the sheet surface can be increased, which improves the adhesion between the sheet and the metal foil and improves the peel strength of the adhesive surfaces.
[0063] In addition, when PTFE is used as the fluororesin, oxygen or nitrogen functional groups are unlikely to be formed in PTFE even when plasma treated, but the presence of silica particles allows the silica surface to have functional groups derived from the surface treatment. As a result, the oxygen atom ratio on the sheet surface can be increased, improving the adhesion between the sheet and metal foil such as copper foil, and improving the peel strength of the adhesive surface.
[0064] Furthermore, by using alumina particles together with silica particles, the silica particles are present at a greater extent on the sheet surface than when silica particles are used alone, and the silica surface can be provided with more functional groups derived from the surface treatment, thereby improving the adhesion between the sheet and the metal foil and increasing the peel strength. Furthermore, even if the silica particles are not surface-treated or the amount of surface treatment is small, by using silica particles in combination with alumina particles, the silica particles are more present on the sheet surface than when silica particles are used alone, and the peel strength of the adhesive surface between the sheet and the metal foil is increased.
[0065] The shape of the silica particles is not particularly limited, but it is particularly preferred that the silica particles are spherical. The spherical shape is preferred because it is easy to process uniformly during drilling, has a small specific surface area, and has low transmission loss. In the present disclosure, it is most preferred to use spherical silica.
[0066] The spherical silica means that the particle shape is close to a perfect sphere, and specifically, the sphericity is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. The sphericity is calculated by taking a photograph with an SEM and calculating the value from the area and perimeter of the observed particle as (sphericity) = {4π x (area) ÷ (perimeter) 2}. The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is used.
[0067] The spherical silica used in the present disclosure preferably has a D90 / D10 of 2 or more (preferably 2.3 or more, 2.5 or more) and a D50 of 10 μm or less when the volume is integrated from the smallest particle size. Furthermore, it is preferable that the D90 / D50 is 1.5 or more (more preferably 1.6 or more). It is preferable that the D50 / D10 is 1.5 or more (more preferably 1.6 or more). It is more preferable that the D50 is 5 μm or less. Since the small particle size spherical silica can enter the gaps between the large particle size spherical silica, it is possible to achieve excellent filling properties and high fluidity. In particular, it is preferable that the particle size distribution has a high frequency on the side of small particle size compared to a Gaussian curve. The particle size can be measured by a laser diffraction scattering type particle size distribution measuring device. In addition, since coarse particles make it difficult to form a thin sheet, it is preferable that the coarse particles having a particle size of a certain size or more are removed by a filter or the like.
[0068] The above-mentioned spherical silica preferably has a water absorption of 1.0% or less, more preferably 0.50% or less. The water absorption is based on the mass of the silica particles when dry. The water absorption is measured by leaving a dry sample at 40°C and 80% RH for 1 hour, and measuring the water generated by heating at 200°C using a Karl Fischer water content meter, and then calculating the water absorption.
[0069] In addition, each parameter of the spherical silica can also be measured using the above-mentioned method after heating the sheet at 600°C for 30 minutes in an air atmosphere to burn off the fluororesin and extracting the spherical silica particles.
[0070] The silica particles are preferably surface-treated in advance, which can induce interactions between the silica particles and reduce the linear expansion coefficient of the sheet. In addition, the peel strength is increased.
[0071] The surface treatment is not particularly limited, and any known surface treatment can be used.Specific examples include treatment with a silane coupling agent such as epoxysilane, aminosilane, isocyanatesilane, vinylsilane, acrylicsilane, hydrophobic alkylsilane, phenylsilane, and fluorinated alkylsilane having a reactive functional group, plasma treatment, and fluorination treatment.Among them, treatment with a silane coupling agent is preferred.
[0072] In the present disclosure, it is preferable to use silica particles treated with a silane coupling agent. By treating silica particles with a silane coupling agent, the linear expansion coefficient can be reduced, which is advantageous in that it improves adhesion to copper foil. In addition, by treating with a silane coupling agent, the polar functional groups present on the silica particle surface react, and the amount of polar functional groups is reduced, resulting in excellent electrical properties. Furthermore, the functional groups contained in the silane coupling agent react with the copper foil surface, thereby increasing the peel strength with the copper foil.
[0073] Examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, isocyanate silanes such as 3-isocyanatepropyltrimethoxysilane, vinyl silanes such as vinyltrimethoxysilane, and acrylic silanes such as acryloxytrimethoxysilane.
[0074] The average particle size of the silica particles is preferably 10 μm or less, which is preferable because the surface roughness of the sheet is low when the average particle size of the silica particles is 10 μm or less. The upper limit of the average particle size of the silica particles is more preferably 8 μm or less, and further preferably 5 μm or less. In addition, the lower limit of the average particle size of the silica particles is not particularly limited, but is preferably 0.5 μm or more. If the average particle size is less than 0.5 μm, the filler tends to aggregate, making it difficult to obtain a sufficient effect. The average particle size here is the D50 value measured by a laser analysis type particle size distribution analyzer.
[0075] The silica particles may be commercially available silica particles that satisfy the above-mentioned properties. Examples of commercially available silica particles include Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), Excelica (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica particles Admafine (manufactured by Admatechs Co., Ltd.), Admanano (manufactured by Admatechs Co., Ltd.), and Admafuse (manufactured by Admatechs Co., Ltd.).
[0076] The shape of the alumina particles is not particularly limited, and examples thereof include spherical, plate-like, and cubic shapes.
[0077] The alumina particles preferably have an average particle size of 10 μm or less, which is preferable because the surface roughness of the sheet is low when the alumina particles have an average particle size of 10 μm or less. The upper limit of the average particle size of the alumina particles is more preferably 5 μm or less, and further preferably 4 μm or less. In addition, the lower limit of the average particle size of the alumina particles is not particularly limited, but is preferably 0.5 μm or more. If the average particle size is less than 0.5 μm, the filler tends to aggregate, making it difficult to obtain a sufficient effect. The average particle size here is the D50 value measured by a laser analysis type particle size distribution analyzer. The alumina particles may or may not be surface-treated.
[0078] The mass ratio of the alumina particles is preferably 10% to 50% based on the total amount of the silica particles and the alumina particles, more preferably 12% to 40%, and even more preferably 13% to 35%. This range is advantageous in that it maintains a low dielectric constant, low loss, and low linear expansion coefficient while providing good adhesion to the metal foil.
[0079] The alumina particles may be commercially available alumina particles that satisfy the above-mentioned properties, such as LS-210B and LS-110F manufactured by Nippon Light Metal Co., Ltd.
[0080] The content of the silica particles and alumina particles in the total amount of the sheet is preferably 30% by mass or more, which is preferable in that the linear expansion coefficient can be reduced while maintaining the dielectric constant and low loss. The blending amount is more preferably 35% by mass or more, even more preferably 50% by mass or more, and even more preferably 55% by mass or more. The upper limit of the blending amount is not particularly limited, but is preferably 70% by mass or less, more preferably 68% by mass or less, and even more preferably 65% by mass or less.
[0081] (Sheet) The sheet of the present disclosure preferably has a dielectric loss tangent of 0.0015 or less at 10 GHz. By setting the dielectric loss tangent within this range, it is preferable that the loss of electrical signals in the circuit can be suppressed. The dielectric loss tangent is more preferably 0.0012 or less, and even more preferably 0.0011 or less. On the other hand, the lower limit of the dielectric loss tangent is preferably 0.00001.
[0082] The sheet of the present disclosure preferably has a relative dielectric constant of 3.5 or less at 10 GHz. Having the relative dielectric constant within this range is preferable in terms of low dielectric loss. The upper limit of the relative dielectric constant is more preferably 3.2, and even more preferably 3.1, while the lower limit of the relative dielectric constant is preferably 2.0, and more preferably 2.5.
[0083] In this specification, the relative permittivity (Dk) and dielectric loss tangent (Df) at 10 GHz were determined by measuring Dk and Df at 25° C. and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab).
[0084] The sheet of the present disclosure preferably has a thickness of 5 to 250 μm. The lower limit of the thickness is more preferably 15 μm or more, and even more preferably 30 μm or more. The upper limit of the thickness is more preferably 230 μm or less, and even more preferably 200 μm or less. The thickness can be selected in consideration of the balance between the electrical properties and the linear expansion coefficient of the laminate.
[0085] The sheet of the present disclosure may contain components other than the fluororesin and silica particles. The components to be contained are not particularly limited, and examples thereof include fluorine-free thermosetting resins and thermoplastic resins. The sheet of the present disclosure preferably does not contain glass fibers. By not containing glass fibers or cloth made of glass fibers, the sheet can be made thinner, and has the advantage of being more flexible and easy to use in applications where it is used while being bent.
[0086] (Sheet manufacturing method) The sheet of the present disclosure can be obtained, for example, by mixing the above-mentioned fluororesin particles and two or more kinds of filler particles to form a film, and then performing a surface treatment. The method for forming the film is not limited, but can be paste extrusion molding, powder rolling molding, etc.
[0087] As described above, it is preferable to use non-melt processable fluororesin particles as the fluororesin particles used in the sheet of the present disclosure. When using such fluororesin particles, it is preferable to form them into a sheet by fibrillating powdered PTFE as a raw material.
[0088] The powdered PTFE preferably has a primary particle size of 0.05 to 10 μm. The use of such a powder has the advantage of excellent moldability and dispersibility. The primary particle size here is a value measured in accordance with ASTM D 4895.
[0089] The powdered PTFE preferably contains 50% by mass or more, more preferably 80% by mass or more, of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. By containing PTFE having a secondary particle diameter of 500 μm or more within this range, it is advantageous in that a sheet with high strength can be produced. By using PTFE with a secondary particle size of 500 μm or more, a sheet with lower resistance and excellent toughness can be obtained.
[0090] The lower limit of the secondary particle diameter is more preferably 300 μm, and even more preferably 350 μm. The upper limit of the secondary particle diameter is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle diameter can be determined, for example, by a sieving method.
[0091] The powdered PTFE has an average primary particle size of preferably 50 nm or more, more preferably 100 nm or more, even more preferably 150 nm or more, and particularly preferably 200 nm or more, since this allows the production of a sheet with higher strength and excellent homogeneity. The larger the average primary particle diameter of PTFE, the more suppressed the increase in paste extrusion pressure when the powder is used for paste extrusion molding, and the better the moldability. The upper limit is not particularly limited, but may be 500 nm. From the viewpoint of productivity in the polymerization step, it is preferably 350 nm.
[0092] The above average primary particle diameter can be determined by preparing a calibration curve of the transmittance of 550 nm projected light per unit length of an aqueous dispersion of PTFE obtained by polymerization, the polymer concentration of which is adjusted to 0.22% by mass, and the average primary particle diameter determined by measuring the unidirectional diameter in a transmission electron microscope photograph, measuring the above transmittance for the aqueous dispersion to be measured, and then based on the calibration curve.
[0093] The PTFE particles used in the present disclosure may have a core-shell structure.The PTFE particles having a core-shell structure may include modified polytetrafluoroethylene, which contains a core of high molecular weight polytetrafluoroethylene and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene in the particle.The modified polytetrafluoroethylene may include, for example, the polytetrafluoroethylene described in JP-A-2005-527652.
[0094] The specific methods for the above paste extrusion molding and powder rolling molding are not particularly limited, but the general methods are described below.
[0095] (Paste extrusion molding) The method for producing the sheet may include a step (1a) of mixing powdered fluororesin particles obtained by using a hydrocarbon-based surfactant, two or more types of filler particles, and an extrusion aid, a step (1b) of paste extrusion molding the resulting mixture, a step (1c) of rolling the extrudate obtained by extrusion molding, a step (1d) of drying the rolled sheet, and a step (1e) of firing the dried sheet to obtain a molded product. The paste extrusion molding can also be carried out by adding conventionally known additives such as pigments and fillers to the fluororesin particles and filler particles.
[0096] The extrusion aid is not particularly limited, and generally known ones can be used, such as hydrocarbon oils.
[0097] (Powder rolling molding) The sheet can also be formed by powder rolling. Powder rolling is a method of applying a shear force to powdered fluororesin particles to fibrillate them and form them into a sheet. The method may then include a step of sintering the particles to obtain a molded product. More specifically, A step (1) of applying a shear force to a raw material composition containing fluororesin particles and filler particles while mixing the raw material composition. A step (2) of forming the mixture obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture obtained in the step (2) into a sheet. The above-mentioned manufacturing method can be used to obtain the above-mentioned polymerizable compound. The method may further include a step (4) of firing the sheet-like material obtained above at 200 to 400° C. for 1 to 60 minutes. Additionally, step (2) may be omitted.
[0098] When a sheet is manufactured by the powder rolling molding method, it is preferable to form a film using a composition that does not contain a liquid component and is essentially composed of fluororesin particles and two or more types of filler particles. Here, "essentially composed of fluororesin particles and two or more types of filler particles" means that the content of components other than the fluororesin particles and the filler particles is 3 mass% or less based on the total amount of the composition.
[0099] The sheet before surface treatment obtained by the above-mentioned sheet manufacturing method preferably has an oxygen element ratio of 1.50 atomic % or more at least on the surface to be surface-treated, as measured by X-ray photoelectron spectroscopy (XPS). The presence of oxygen element on the surface of the sheet before surface treatment enables good adhesion to a metal foil having a smooth surface. In addition, such a range is preferable in order to set the oxygen element ratio of the sheet after surface treatment in the above-mentioned specific range as measured by X-ray photoelectron spectroscopy (XPS). The oxygen atomic ratio is preferably 1.65 atomic % or more, more preferably 1.70 atomic % or more, and even more preferably 1.80 atomic % or more. There is no particular upper limit, but in consideration of the effect on productivity and other physical properties, it is preferably 4.90 atomic % or less. The method for adjusting the oxygen element ratio of the sheet before the surface treatment to fall within the above range is not particularly limited, and may be controlled, for example, by adjusting the blending amount of filler particles or the molding method.
[0100] When silica particles are used as one of the filler particles, the silicon element ratio of the sheet before surface treatment is preferably 0.2 atomic % or more at least on the surface to be surface treated, as measured by X-ray photoelectron spectroscopy (XPS). The presence of silicon element on the surface of the sheet before surface treatment enables good adhesion to the gold foil, which has a smooth surface. This range is also preferable so that the silicon element ratio of the sheet after surface treatment is preferably 0.50 atomic % or more as measured by X-ray photoelectron spectroscopy (XPS). The silicon element ratio is preferably 0.30 atomic % or more, more preferably 0.50 atomic % or more, and even more preferably 0.70 atomic % or more. There is no particular upper limit, but in consideration of the effect on productivity and other physical properties, it is preferably 2.0 atomic % or less. The silicon element ratio of the sheet before surface treatment can be adjusted to fall within the above range by, for example, adjusting the blending amount of silica particles.
[0101] (Surface treatment) By subjecting one or both sides of the sheet obtained by the above method to a surface treatment under appropriate conditions, a sheet satisfying the above requirements can be obtained. Generally, it is difficult for a fluororesin to adhere to a metal foil. For this reason, in the present disclosure, the sheet is subjected to a surface treatment in order to improve the lamination properties. Generally, such a surface treatment is performed by increasing the amount of oxygen atoms on the resin surface.
[0102] The specific method for the above surface treatment is not particularly limited, and any known method can be used. The surface treatment of the sheet can be a conventional discharge treatment such as plasma discharge treatment, corona discharge treatment, glow discharge treatment, sputtering treatment, etc. Among these, plasma treatment is preferable.
[0103] The plasma treatment is a treatment in which the sheet is brought into contact with plasma to etch the fluororesin on the outer surface of the sheet and add oxygen atoms, nitrogen atoms, etc. to the outer surface of the sheet. For example, the surface free energy can be controlled by introducing oxygen gas, nitrogen gas, hydrogen gas, helium gas, argon gas, or the like into the discharge atmosphere.
[0104] Alternatively, the surface to be modified may be exposed to an atmosphere of an organic compound-containing inert gas, which is an inert gas containing an organic compound, and a high-frequency voltage is applied between the electrodes to cause a discharge, thereby generating active species on the surface, and then the surface treatment may be performed by introducing a functional group of the organic compound or graft polymerizing a polymerizable organic compound.
[0105] The organic compound in the organic compound-containing inert gas includes polymerizable or non-polymerizable organic compounds containing oxygen atoms, such as vinyl esters such as vinyl acetate and vinyl formate; acrylic esters such as glycidyl methacrylate; ethers such as vinyl ethyl ether, vinyl methyl ether, and glycidyl methyl ether; carboxylic acids such as acetic acid and formic acid; alcohols such as methyl alcohol, ethyl alcohol, phenol, and ethylene glycol; ketones such as acetone and methyl ethyl ketone; carboxylic esters such as ethyl acetate and ethyl formate; acrylic acids such as acrylic acid and methacrylic acid. Among these, vinyl esters, acrylic esters, and ketones are preferred because the modified surface is less likely to be deactivated, that is, has a long life. In particular, vinyl acetate and glycidyl methacrylate are preferred.
[0106] The concentration of the organic compound in the organic compound-containing inert gas varies depending on the type of the organic compound, the type of fluororesin to be surface-treated, etc., but is usually 0.1 to 3.0% by volume, preferably 0.1 to 1.0% by volume, more preferably 0.15 to 1.0% by volume, and even more preferably 0.30 to 1.0% by volume. The discharge conditions may be appropriately selected depending on the desired degree of surface treatment, the type of fluororesin, the type and concentration of the organic compound, etc. Usually, the discharge amount is 50 to 1500 W·min / m 2 , preferably 70 W·min / m 2 More than 1400W min / m 2 Discharge treatment is carried out within the following range. The treatment temperature can be any temperature within the range of 0° C. to 100° C. A temperature of 80° C. or less is preferable to prevent stretching or wrinkling of the sheet.
[0107] The sheet manufacturing method of the present disclosure is characterized in that, for example, when silica particles and alumina particles are used as the filler particles, the fluororesin particles are mixed with the silica particles and the alumina particles to form a film, and then the above-mentioned surface treatment is performed. In addition, the manufacturing method of the sheet of the present disclosure is characterized in that a film is formed using a composition substantially consisting of fluororesin particles and filler particles including at least silica particles and alumina particles, and then the surface is treated.
[0108] The sheet of the present disclosure that has been surface-treated as described above can be used as a sheet for a circuit board by laminating it with a metal foil. A laminate may be formed by adhering a metal foil to one or both sides of the above-mentioned sheet. The present disclosure also relates to a metal clad laminate having the above-mentioned sheet as an essential layer and having a metal foil layer on one or both sides. As described above, the sheet containing the fluororesin and two or more types of filler particles of the present disclosure has excellent adhesiveness, and therefore a laminate in which the surface-treated surface of the sheet of the present disclosure is directly laminated onto a metal foil is preferred.
[0109] Examples of the metal foil used in the present disclosure include copper foil, gold foil, silver foil, platinum foil, ruthenium foil, etc. Among these, copper foil is preferred because it has low conductor loss.
[0110] The copper foil preferably has a surface roughness (Rz) of 2.0 μm or less. If the surface roughness (Rz) is 2.0 μm or less, the interface between the copper foil and the sheet becomes smooth, and transmission loss is low, which is preferable. The copper foil may have at least a surface that is bonded to the above-mentioned sheet with an Rz of 2.0 μm or less, and the other surface is not particularly limited in Rz. The sheet of the present disclosure has excellent adhesion to copper foil having a high smoothness of Rz 2.0 μm or less, further Rz 1.0 μm or less, and even further Rz 0.5 μm or less.
[0111] The above Rz is the sum of the highest point (maximum peak height: Rp) and the deepest point (maximum valley depth: Rv). The above Rz is the ten-point average roughness defined in JIS-B0601. In this specification, the above Rz is a value measured using a surface roughness meter (product name: Surfcom 470A, manufactured by Tokyo Seiki Co., Ltd.) with a measurement length of 4 mm.
[0112] The copper foil preferably has a surface roughness (Rq) of 0.010 to 0.15 μm. It is preferable that Rq is within the above range since the transmission loss can be reduced satisfactorily. The copper foil may have an Rq of 0.01 to 0.15 μm on at least the surface that is bonded to the above-mentioned sheet, and the Rq of the other surface is not particularly limited. The Rq of the surface that is bonded to the sheet is more preferably 0.015 to 0.1 μm, and further preferably 0.03 to 0.08 μm. The above Rq is the root mean square height. In this specification, the above Rq is a value measured with a stylus surface roughness measuring instrument (product name: SE600A, manufactured by Kosaka Laboratory) with a measurement length of 4 mm.
[0113] The thickness of the copper foil is not particularly limited, but is preferably 1 to 100 μm, more preferably 5 to 50 μm, and even more preferably 9 to 35 μm.
[0114] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0115] The copper foil having Rz of 2.0 μm or less and / or Rq of 0.01 to 0.15 μm is not particularly limited, and commercially available products can be used. Examples of such commercially available copper foils include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm / Rq 0.05 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.).
[0116] The copper foil may be surface-treated to increase the peel strength with the sheet of the present disclosure.
[0117] The surface treatment is not particularly limited, but may be a silane coupling treatment, a plasma treatment, a corona treatment, a UV treatment, an electron beam treatment, etc., and the reactive functional group of the silane coupling agent is not particularly limited, but from the viewpoint of adhesion to the resin substrate such as the sheet of the present disclosure, it is preferable to have at least one selected from an amino group, a (meth)acrylic group, a mercapto group, and an epoxy group at the end. In addition, the hydrolyzable group is not particularly limited, but may be an alkoxy group such as a methoxy group or an ethoxy group. The copper foil used in the present disclosure may have an anti-rust layer (such as an oxide film such as chromate), a heat-resistant layer, etc. formed thereon.
[0118] The surface-treated copper foil having a surface treatment layer of the above-mentioned silane compound on the copper foil surface can be produced by preparing a solution containing the silane compound and then surface treating the copper foil with this solution.
[0119] The copper foil may have a roughening treatment layer on the surface thereof from the viewpoint of improving adhesion to a resin substrate. In addition, if there is a risk that the roughening treatment will degrade the performance required in the present disclosure, the amount of roughening particles electrodeposited on the copper foil surface can be reduced as necessary, or the roughening treatment can be omitted.
[0120] Between the copper foil and the surface treatment layer, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proofing treatment layer, and a chromate treatment layer may be provided in order to improve various properties. These layers may be a single layer or multiple layers.
[0121] When the metal clad laminate of the present disclosure is formed by directly laminating the surface-treated surface of the sheet and a copper foil, the peel strength of the interface between the copper foil and the sheet is preferably 1 kN / m or more. By using the sheet of the present disclosure, the above-mentioned peel strength can be achieved. By setting the peel strength at 1 kN / m or more, the sheet can be suitably used as a metal-clad laminate or a circuit board, and the peel strength is preferably 1.2 kN / m or more. The upper limit of the peel strength is not particularly limited, but may be 3.0 kN / m or less. The peel strength here means the peel strength measured under the conditions described in the Examples.
[0122] In the case of a laminate in which a copper foil is bonded to the surface-treated surface of a sheet that has been surface-treated on only one side, a separate surface treatment may be applied to the untreated side of the sheet in order to improve adhesion between the laminate and other materials.
[0123] The metal clad laminate of the present disclosure may further include layers other than the above-mentioned sheet and metal foil. The layer other than the sheet and the metal foil is preferably a layer made of at least one resin selected from the group consisting of polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, and polybutadiene.
[0124] The layer made of the resin, which is a layer other than the sheet and the metal foil, may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable.
[0125] The layers other than the metal foil and the sheet are not particularly limited as long as they are made of the above-mentioned resins. The layers other than the sheet and the metal foil preferably have a thickness of 12.5 to 260 μm.
[0126] In the metal clad laminate of the present disclosure, the metal foil layer may be formed on one or both sides of the rolled sheet. Methods for forming the metal foil layer include a method of laminating (adhering) a metal foil to the surface of the rolled sheet, a vapor deposition method, a plating method, and the like. The method for laminating the metal foil includes a method using heat pressing, etc. The heat pressing temperature is from the melting point of the sheet -150°C to the melting point of the sheet +40°C. The heat pressing time is, for example, 1 to 30 minutes.
[0127] For example, a method is suitable in which the above sheet and metal foil are laminated together, heated at 180 to 390° C., and press-molded at a pressure of 0.5 to 5 MPa in vacuum or in an inert gas atmosphere to produce a copper clad laminate. By performing press molding under these conditions, the sheet does not deteriorate and can be bonded to copper foil.
[0128] The method for producing a metal clad laminate of the present disclosure is characterized in that the above sheet and copper foil are laminated together, heated at 180 to 390°C, and press molded at a pressure of 0.5 to 5 MPa under vacuum or in an inert gas atmosphere.
[0129] When obtaining the above-mentioned laminate configuration, the sheet of the present disclosure is used by adhering copper foil to one or both sides. As described above, the sheet of the present disclosure has excellent adhesiveness. Therefore, it also has excellent adhesiveness to copper foil having a high smoothness of Rz 2.0 μm or less.
[0130] Conventionally, copper foils used for circuit boards have been given a certain degree of unevenness on their surfaces to ensure adhesion to insulating layers. However, in high-frequency applications, the presence of unevenness on the surface of copper foils is undesirable because it causes loss of electrical signals. The above laminate can obtain suitable adhesion even to copper foils with high smoothness, and is a laminate that can be suitably used as a circuit board.
[0131] The metal clad laminate of the present disclosure is not particularly limited in its application, and is used as a circuit board. The present disclosure also relates to a circuit board having the metal clad laminate. A circuit board is a plate-like component for electrically connecting electronic components such as semiconductors and capacitor chips and simultaneously arranging and fixing them in a limited space. There is no particular limitation on the configuration of a circuit board formed from the sheet or metal clad laminate of the present disclosure. The circuit board may be any of a rigid board, a flexible board, and a rigid-flexible board. The circuit board may be any of a single-sided board, a board, a double-sided board, and a multilayer board (such as a pulled-up board). In particular, it can be suitably used for flexible boards and rigid boards. When the sheet of the present disclosure does not contain glass fiber or a cloth made of glass fiber, it is suitable for flexible boards. In particular, it can be suitably used as a printed circuit board for high frequencies of 10 GHz or more.
[0132] In this disclosure, the high-frequency circuit does not only refer to a circuit that transmits only high-frequency signals, but also includes a circuit that has a transmission line that converts a high-frequency signal into a low-frequency signal and outputs the generated low-frequency signal to the outside, a transmission line for supplying power to drive high-frequency compatible components, and other transmission lines that transmit signals other than high-frequency signals, which are arranged on the same plane.The circuit can also be used as a circuit board for an antenna, a filter, etc. The present disclosure also relates to an antenna formed from the circuit board, and is particularly suitable as a millimeter wave antenna for mobility such as automobiles and aircraft.
[0133] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned metal clad laminate.
[0134] The sheet and metal clad laminate of the present disclosure are used as electric and electronic components, for example, antennas used in electronic devices and communication devices such as ETC, GPS, wireless LAN, and mobile phones, high-speed transmission connectors, CPU sockets, millimeter wave and quasi-millimeter wave radars such as collision prevention radars, RFID tags, capacitors, inverter parts, cable covering materials, insulating materials for secondary batteries such as lithium ion batteries, speaker diaphragms, etc.
[0135] Examples of high-speed communication-compatible substrates include base station antenna substrates, antenna distribution substrates, substrates for RRH (Remote Radio Head) which is the radio part of a wireless base station, substrates for the control part or baseband part (BBU: Base Band Unit) of a wireless base station, transceiver substrates for high-speed communication, substrates for RNC (Radio Network Controller), substrates for high-speed transmitters, substrates for high-speed receivers, substrates for high-speed signal multiplexing circuits, substrates for WiFig using the 60 GHz band, substrates for data transfer used in servers for data centers, etc. Examples of high-speed communication-compatible substrates include antenna substrates, for example, substrates for massive multi-element antennas (Massive MIMO) for large-capacity communication required by standards after 5G. Furthermore, examples include receiving antennas for space-transmission wireless power supply using microwaves. The sheet of the present disclosure has good adhesion to unroughened copper foil, which has low transmission loss, and therefore is particularly suitable for antennas, since when a copper-clad laminate containing the sheet of the present disclosure and unroughened copper foil is processed to obtain an antenna, the gain is improved.
[0136] The sheet of the present disclosure can be used not only as an insulator for a substrate but also as an insulator for a signal line coating material, for example, as an insulating coating material (e.g., insulating tube) for a waveguide for transmitting high-speed signals, a QSFP cable for a high-speed LAN, a coaxial cable for high-speed communication (e.g., SFP+ cable, QSFP+ cable, etc.), a coaxial cable for low loss, etc.
[0137] When using such high frequencies, materials used in electrical components such as connectors and communication devices such as casings are required to have stable electrical properties such as low relative dielectric constant (εr) and low dielectric tangent (tanδ). The sheet of the present disclosure can also be used as an insulating material for such materials.
[0138] The sheet of the present disclosure can also be used as an insulating material for connector printed wiring boards that require soldering. The sheet of the present disclosure has excellent heat resistance, so problems are unlikely to occur even at high temperatures during soldering.
[0139] In dielectric waveguides, materials with low dielectric loss are required to transmit high-frequency millimeter waves or submillimeter waves with low loss. The sheet of the present disclosure can also be used as an insulating material for dielectric waveguides that transmit millimeter waves, submillimeter waves, etc. Examples of dielectric waveguides include cylindrical dielectric lines, rectangular dielectric lines, elliptical dielectric lines, tubular dielectric lines, image lines, insulator image lines, trapped image lines, rib guides, strip dielectric lines, inverted strip lines, H guides, nonradiative dielectric lines (NRD guides), etc.
[0140] In this disclosure, mobility refers to all means and methods related to movement and transportation, including automobiles in general, such as private cars, buses, taxis, and trucks, as well as two-wheeled vehicles, such as motorcycles, bicycles, and mopeds, railways, senior cars, and compact personal mobility vehicles for one person.Mobility is not necessarily limited to vehicles that move on the ground, and may also be vehicles that move in the air or underwater.
[0141] The laminate for a circuit board may further include a base layer in addition to the metal foil layer and the above-mentioned sheet. The base layer is not particularly limited, but examples thereof include a fabric layer made of glass fiber and a resin film layer.
[0142] The resin film used as the substrate layer is preferably a heat-resistant resin film or a thermosetting resin film. Examples of the heat-resistant resin film include polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, etc. Examples of the thermosetting resin include those containing epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, polybutadiene, etc. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable.
[0143] The heat-resistant resin film and the thermosetting resin film are not particularly limited in terms of dielectric properties, linear expansion coefficient, water absorption coefficient, and other properties, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and even more preferably 3.2 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and even more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and even more preferably 40 ppm / °C or less. The water absorption coefficient is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less.
[0144] When the metal clad laminate, which essentially contains the above-mentioned sheet and metal foil, is laminated with a base layer such as a resin film layer, the sheet layer side of the metal clad laminate can be adhered to the base layer. In this case, the sheet layer side of the copper clad laminate may be surface-treated before lamination to enhance adhesion performance. The surface treatment here is not particularly limited, and examples thereof include the above-mentioned plasma treatment.
[0145] In the above laminate, the order in which the metal foil layer, the substrate, and the above-mentioned sheets are laminated and the manufacturing method are not particularly limited, and a layer configuration according to the purpose can be adopted. Specific examples of the above-mentioned stacking order include a base layer / sheet / metal foil layer, a metal foil layer / sheet / base layer / sheet / metal foil layer, and a metal foil layer / base layer / sheet / base layer / metal foil layer. If necessary, other layers may also be included. EXAMPLES
[0146] The present disclosure will be specifically described below based on examples. However, the present invention is not limited to the following examples. In the following examples, "parts" and "%" respectively represent "parts by mass" and "% by mass" unless otherwise specified.
[0147] Each of the obtained samples was evaluated based on the following criteria.
[0148] [Sheet thickness] Measurements were taken using a micrometer.
[0149] [XPS measurement of sheet surface] The measurements were performed using a scanning X-ray photoelectron spectroscopy (XPS / ESCA) PHI5000VersaProbeII (ULVAC-PHI, Inc.).
[0150] [Coefficient of linear expansion (CTE) of sheet] TMA measurements were performed in tensile mode using a TMA-7100 (Hitachi High-Tech Science Corporation). A sheet cut to a length of 20 mm, width of 5 mm, and thickness of 150 μm was used as a sample piece. The distance between the chucks was set to 10 mm, and the linear expansion coefficient was calculated from the displacement of the sample from 0 to 150°C at a heating rate of 2°C / min while applying a load of 49 mN.
[0151] [Dissipation factor of sheet] The dielectric loss tangent was measured at 20°C and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (EM Lab).
[0152] [Static contact angle of sheet with water] The static contact angle of the prepared sheet to water was measured using a contact angle meter (Kyowa Interface Science Co., Ltd., "DropMaster") at 23° C., with a droplet amount of 2 μL, one second after the droplet landed.
[0153] [Peel Strength] After the surface treatment, copper foil (CF-T9DA-SV-18, Rz = 0.85 μm, Rq = 0.05 μm, manufactured by Fukuda Metal Foil Powder Co., Ltd.) was placed on top and bottom of the sheet so that the treated surfaces were in close contact with the sheet, and the sheet was then pressurized and heated in a vacuum heat press (360°C, 2.5 MPa, 300 s) to prepare a sample. The obtained sample was cut into a strip of 10 mm width, and the peel strength was measured using a Tensilon universal testing machine (manufactured by Shimadzu Corporation) by gripping the unbonded portion of the strip sample with the upper and lower chucks of the Tensilon and pulling it at a speed of 50 mm per minute, and the obtained value was taken as the peel strength.
[0154] <How to make sheets A to N> (Paste extrusion molding) PTFE powder (average particle size: 500 μm, apparent density: 460 g / L, standard specific gravity: 2.17) and silica particles shown in Table 1 were weighed out to have the mass ratio shown in Table 1, and mixed in a mixer in the presence of dry ice. The temperature during mixing was -10°C or lower. 21% oil (Isopar H) was added to the obtained mixed powder, mixed, and aged for about 5 hours. The aged composition was preformed under a pressure of 3 MPa, and the preformed body was extruded at 40° C. and 50 mm / min to obtain an extrusion sample. The extruded sample was rolled with two rolls (roll gap: set to 500 to 80 μm) to obtain a sample with a film thickness of 125 μm, and dried at 200° C. for 2 hours to obtain a sheet.
[0155] <How to make Sheet O> (Powder rolling molding) PTFE powder (average particle size: 500 μm, apparent density: 460 g / L, standard specific gravity: 2.17), silica particles, and alumina particles were weighed out to obtain the mass ratio shown in Table 1, and stirred in a Wonder Crusher at room temperature with a setting of 6 for 30 seconds twice. The resulting mixture was rolled with two rolls (roll gap: set to 100 μm, roll temperature: 100° C.) to obtain a sample with a film thickness of 130 μm.
[0156] In addition, the silica used in each example was spherical silica, as shown in Table 1, SC6500-SQ (average particle size 2.1 μm) manufactured by Admatechs Co., Ltd., and SC6500-SQ (average particle size 2.1 μm) manufactured by Admatechs Co., Ltd. that had been surface-treated with 3-aminopropyltriethoxysilane (treatment amount of 0.2 mass% based on the mass of silica particles). As the alumina, LS-210B (average particle size: 3.1 μm) and LS-110F (average particle size: 1.1 μm) manufactured by Nippon Light Metal Co., Ltd. were used as shown in Table 1.
[0157] [Table 1]
[0158] (Examples 1 to 13) (Seat surface treatment) A sheet was placed between the upper and lower electrodes in a treatment chamber (direct type plasma surface treatment device, manufactured by Air Water Corporation) equipped with upper and lower electrodes, and the inside of the treatment chamber was filled with a mixed gas atmosphere of argon, helium, nitrogen and oxygen.The sheet surface was then subjected to discharge plasma treatment for the treatment time shown in Table 2. The elemental composition of the surface-treated sheet was measured by XPS.
[0159] Comparative Example 1 For sheet A, no surface treatment was performed, and the elemental composition was measured by XPS.
[0160] (Comparative Examples 2 and 3) The sheet surfaces were subjected to discharge plasma treatment in the same manner as in Example 1, except that sheets M and N were used. The elemental composition of the surface-treated sheet was measured by XPS.
[0161] The results of Examples 1 to 13 and Comparative Examples 1 to 3 are shown in Table 2.
[0162] [Table 2]
[0163] From the above experimental results, it can be seen that the sheets of the examples can be well bonded to highly smooth copper foil while maintaining a low dielectric tangent and low CTE, and can be suitably used as circuit board materials. [Industrial Applicability]
[0164] The sheet of the present disclosure can be suitably used in a metal clad laminate for a circuit board.
Claims
1. A sheet containing a fluororesin and two or more types of filler particles, The sheet is characterized in that one or both sides thereof have an oxygen element ratio of 3.0 atomic % or more as measured by X-ray photoelectron spectroscopy (XPS) and a coefficient of linear expansion (CTE) of 70 ppm / ° C. or less.
2. 2. The sheet according to claim 1, wherein the fluororesin is polytetrafluoroethylene.
3. 3. The sheet according to claim 1, wherein the nitrogen element ratio measured by X-ray photoelectron spectroscopy (XPS) is 0.85 atomic % or more.
4. 3. The sheet according to claim 1, wherein the silicon element ratio of said surface is 0.50 atomic % or more when measured by X-ray photoelectron spectroscopy (XPS).
5. 3. The sheet according to claim 1, further comprising a static contact angle of water on said surface of 105[deg.] or less, measured 1 second after a 2 [mu]L droplet landed on said surface.
6. 3. The sheet according to claim 1 or 2, wherein one of the two or more types of filler particles is silica particles.
7. 7. The sheet according to claim 6, wherein the silica particles are spherical silica.
8. 7. The sheet according to claim 6, wherein the silica particles are treated with a silane coupling agent.
9. 7. The sheet according to claim 6, wherein the silica particles have an average particle size of 10 [mu]m or less.
10. 7. The sheet according to claim 6, wherein the filler particles other than silica particles of the two or more types of filler particles are alumina particles.
11. The sheet according to claim 10, wherein the alumina particles have an average particle size of 10 μm or less.
12. The sheet according to claim 10, wherein a mass ratio of the alumina particles to the total amount of the silica particles and the alumina particles is from 10% to 50%.
13. 11. The sheet according to claim 10, wherein the content of the silica particles and alumina particles in the total amount of the sheet is 30 mass % or more.
14. 3. The sheet according to claim 1 or 2, which has a dielectric tangent value of 0.0015 or less at 10 GHz.
15. 3. The sheet according to claim 1 or 2, having a thickness of 5 to 250 μm.
16. A method for producing the sheet according to claim 10, comprising the steps of: mixing fluororesin particles, silica particles, and alumina particles to form a film; and surface-treating the film.
17. A method for producing the sheet according to claim 10, comprising forming a film using a composition substantially consisting of fluororesin particles and filler particles containing at least silica particles and alumina particles, and then performing a surface treatment.
18. 3. A metal-clad laminate comprising the sheet according to claim 1 or 2 as an essential layer and having a metal foil layer on one or both sides.
19. 20. The metal-clad laminate of claim 18, wherein the metal foil is a copper foil.
20. 20. The metal clad laminate according to claim 19, wherein the copper foil has a surface roughness (Rz) of 2.0 μm or less.
21. The metal clad laminate according to claim 19, wherein the surface roughness (Rq) of the copper foil is 0.01 to 0.15 μm.
22. 20. The metal clad laminate according to claim 19, wherein the copper foil and the sheet are directly laminated together, and the peel strength of the interface between the copper foil and the sheet is 1 kN / m or more.
23. A method for producing a metal clad laminate according to claim 19, comprising laminating the sheet according to claim 1 or 2 and a copper foil, heating the laminate at 180 to 390°C, and press-molding the laminate at a pressure of 0.5 to 5 MPa under vacuum or in an inert gas atmosphere.
24. A circuit board comprising the metal clad laminate according to claim 18.
25. 25. An antenna formed from the circuit board of claim 24.
26. 26. The antenna of claim 25, which is a millimeter wave antenna for mobility.
Citation Information
Patent Citations
Printed wiring board for high frequency use
JP2015008260A
Fluororesin film, copper-clad laminate and substrate for circuits
JP2022112028A
Composition and method for producing laminate
JP2023028091A